Development and preliminary research on the measure properties of a perceptual and motor demands assessment protocol for virtual reality systems - Cairolli,Fábio Fabregas (2017)
The virtual reality has been frequently required in rehabilitation settings. However, it still lacks specificity, making it necessary to establish specific criteria to classify the most relevant aspects of electronic games to allow interventions based on virtual reality. Therefore, the purpose of this study is to develop a Perceptual and motor demands assessment protocol for virtual reality systems and to investigate its content validity and intra and inter observer agreement. The protocol was created through a literature review including classical studies as well as a review of recent articles about motor behavior, physical training, cognitive neuroscience and virtual reality. The previous versions were presented in study group meetings and congresses, and modified accordingly to suggestions of experts. Three examiners used the final version to analyze twice the total of 20 videos of individuals in a virtual environment and answered a questionnaire about its content validity. Most of the obtained values were classified as good (concordance from 80% to 89%) or excellent (concordance from 90% to 100%) by the three examiners and the protocols content validity was adequate. The protocol is valid, applicable and practical for analyzing different requirements of electronic games in a virtual environment.